A Record Chromophore Density in High‐Entropy Liquids of Two Low‐Melting Perylenes: A New Strategy for Liquid Chromophores. Issue 4 (15th January 2019) - Kushwaha, Khushbu; Yu, Liyang; Stranius, Kati; Singh, Sandeep Kumar; Hultmark, Sandra; Iqbal, Muhammad Naeem; Eriksson, Lars; Johnston, Eric; Erhart, Paul; Müller, Christian; Börjesson, Karl
Abstract: Liquid chromophores constitute a rare but intriguing class of molecules that are in high demand for the design of luminescent inks, liquid semiconductors, and solar energy storage materials. The most common way to achieve liquid chromophores involves the introduction of long alkyl chains, which, however, significantly reduces the chromophore density. Here, strategy is presented that allows for the preparation of liquid chromophores with a minimal increase in molecular weight, using the important class of perylenes as an example. Two synergistic effects are harnessed: (1) the judicious positioning of short alkyl substituents, and (2) equimolar mixing, which in unison results in a liquid material. A series of 1‐alkyl perylene derivatives is synthesized and it is found that short ethyl or butyl chains reduce the melting temperature from 278 °C to as little as 70 °C. Then, two low‐melting derivatives are mixed, which results in materials that do not crystallize due to the increased configurational entropy of the system. As a result, liquid chromophores with the lowest reported molecular weight increase compared to the neat chromophore are obtained. The mixing strategy is readily applicable to other π‐conjugated systems and, hence, promises to yield a wide range of low molecular weight liquid chromophores. Abstract : A perylene blend, liquid at room temperature, was achieved by mixing two derivatives with similar photophysical properties. The resulting material is the liquid chromophore with the smallest weight increase due to solubilizing substituents presently known. The analysis suggests that the approach of thermodynamic mixing is general, and hence, applicable to any parent compound, yielding liquid chromophores with a minimal weight increase.